El educador, agente necesario de la construcción social - Valle López, Angela del (Pontificia Universidad Católica del Perú. Fondo Editorial, 2008)
In the postmodern society the role of the school and the teacher is strongly conditionedby the social demands of each particular context. The continuous changecannot be stop as it depends on science and technology. It is urgent to understandthat in a human universe that is changing because the performers and their roleschange, the social dynamics and the views of the world change, the central roleof education is to be assumed knowing that in the present historical situation theteacher is the direct subject in the debate. In view of this, we raise the question onwhat is the role of the educator today. The new approaches and demands requirea new professional culture in accord with the educational institution. Education isin need of change on the ways to impart knowledge and the ways of learning; it isin need of competent educators who have a new concept of their own role.

En la sociedad posmoderna la función de la escuela y del docente está fuertementecondicionada por las demandas sociales de cada contexto espacial. Los cambiosson imparables, todo depende de la ciencia y de la tecnología. Urge entender queen un universo humano que cambia —porque cambian sus actores, sus roles, lasdinámicas sociales, las maneras de ver el mundo— hay que asumir que la educaciónse presenta como el eje articulador, cuyo debate en la actual coyunturahistórica apunta directamente al maestro. Ante esto nos preguntamos: ¿cuál es elpapel del educador hoy? Los nuevos planteamientos y exigencias reclaman unanueva cultura profesional coherente con la función de la institución escolar. Laeducación necesita una transformación en los modos de impartir conocimientos,en la manera de aprender; precisa un educador competente. Desde esta claveaportamos algunas ideas en torno al tipo de educador que reclaman los nuevostiempos.
Keywords: Educador; Escuela; Maestro; Enseñanza-Aprendizaje; Educator; School; Teacher; Teaching-Learning; https://purl.org/pe-repo/ocde/ford#5.03.00